2015
DOI: 10.1111/fwb.12644
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of phytoplankton and benthic algae to recent nutrient enrichment in Arctic tundra ponds

Abstract: Summary Tundra ponds are a dominant feature on the Arctic Coastal Plain, but their response to warming, especially in the long‐term, is largely unknown. Our study assessed changes in algal nutrient limitation over a 40‐year period in historically studied ponds that may have been affected by either human development in the region or increased temperatures leading to permafrost thaw and nutrient release. We also compared nutrient limitation of algae in the pelagic and benthic zones at a landscape level. Nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 69 publications
(113 reference statements)
2
12
0
Order By: Relevance
“…The control solution included only deionized water with no added nutrients. The low nutrient solution contained 1.5 mg N/L, 0.6 mg P/L, similar to the maximum observed concentrations at enriched sites ponds within the village of Barrow during the growing seasons between 2010 and 2015 (1.7 mg DIN/L; 0.55 mg TP/L, where DIN = dissolved inorganic nitrogen, Ttotal phosphorus; Lougheed et al, and Lougheed, ). The high nutrient solution contained 7.5 mg N/L, 3.0 mg P/L, which was 5 times higher than the “low” solution.…”
Section: Methodssupporting
confidence: 76%
“…The control solution included only deionized water with no added nutrients. The low nutrient solution contained 1.5 mg N/L, 0.6 mg P/L, similar to the maximum observed concentrations at enriched sites ponds within the village of Barrow during the growing seasons between 2010 and 2015 (1.7 mg DIN/L; 0.55 mg TP/L, where DIN = dissolved inorganic nitrogen, Ttotal phosphorus; Lougheed et al, and Lougheed, ). The high nutrient solution contained 7.5 mg N/L, 3.0 mg P/L, which was 5 times higher than the “low” solution.…”
Section: Methodssupporting
confidence: 76%
“…The relative supply of nutrients from upland environments to surface waters can have important implications for food web properties and consumer productivity (Cross, Benstead, Frost, & Thomas, ; Elser et al, ). The productivity of our study system, like many arctic rivers, is P‐limited, and decreasing P supply may thus be reducing biofilm productivity and nitrate uptake, further driving the increasing ratio of N:P. Changes to nutrient concentrations and nutrient limitation have also been documented in Arctic tundra ponds where Lougheed et al () found increases in dissolved nitrogen and phosphorus and a shift from P to N and P colimitation of benthic biofilms over a 40‐year period. Decreased P concentration in the current study could also be explained by increased uptake by biofilms and thus the removal of P from the water column, rather than a reduced supply of P from upland environments.…”
Section: Discussionmentioning
confidence: 58%
“…As the limiting nutrient of many aquatic ecosystems in the Arctic, changes in the supply of P to surface waters have the potential to greatly alter the structure and function of aquatic ecosystems (Lougheed, ; Slavik et al, ). Our results, however, do not necessarily support the hypothesis that increased exposure of phosphate‐rich mineral soils will leach P into groundwater, ultimately leading to increases in P supply to surface water ecosystems (Frey & McClelland, ; Hobbie et al, ; Pearce et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient addition has been identified as drivers of increased plant biomass in experimental studies in wet and moist tundra (Chapin et al ., ; Shaver et al ., ). In tundra ponds, warmer water temperatures and permafrost thaw have been linked with elevated nutrient availability (Lougheed et al ., ; Heikoop et al ., ; Reyes & Lougheed, ) and algal biomass (Lougheed et al ., ). We assert that thawing permafrost is also contributing to elevated plant biomass in aquatic habitats of the arctic tundra.…”
Section: Discussionmentioning
confidence: 97%